Aplikasi Pemantauan Nilai dan Presensi Siswa Berbasis Mobile dan Web pada SMP ABC - Bryan Aprian; Bagus Mulyawan; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
ABC’s school is the one of many International school and located in the central of jakarta, Indonesia. ABS’s school have three degree including primary school, junior high school and senior high school. Universal school has two classes in each grades. Each class can provide thirty seats for students to learn.The problem in ABC’s school is the uses of manual method to manage data and make report for the student report card, this process require a lot of time and data can be damage or fault . Nowadays, technology is increasing rapidly, parents and student request the school to provide them with the fast and appropriate informartion. Therefore this application is expected to solved the problem using web and mobile. This Application is made with the programing langguage of Php and Android for the phone. We expect that ABC’s school can integrate their collection of the data and can provide student and parents with fast and appropriate information.